Does language switching behavior rely on general executive functions? - Jylkkä Jussi; Laine Matti; Lehtonen Minna (Cambridge University Press, 2022)
The assumption that everyday language switching trains bilinguals’ executive functions (EF) presupposes that language switching engages domain-general EF. This study examined associations between three types of tasks in a group of Finnish-English late bilinguals: everyday language switching frequency assessed with Ecological Momentary Assessment, language switching performance on a cued bilingual naming task, and EF as measured with Simon, Flanker, and Number-letter tasks. Cued switching performance showed mainly positive associations with EF performance, but the associations between everyday language switching and cued switching performance, and between everyday switching and the EF tasks were largely against our hypotheses. The findings indicate that participants with lower monitoring capacity make more everyday language switches. This speaks against the idea that everyday language switching would facilitate executive functioning. The results suggest that associations between language switching and general EF are more complex than current models assume.